MPT64 gene mutations leading to non-reactivity on a rapid immunochromatographic assay - Ka Lip Chew; Raymond Tzer Pin Lin; Jeanette Woon Pei Teo (Journal of Infection in Developing Countries)
This item has no abstract. Follow the links on the page to access the full text.